FUNCTIONAL ANALYSIS OF AGERATUM CONYZOIDES L. (BABANDOTAN) LEAVES EXTRACT ON RHEUMATOID ARTHRITIS MODEL RAT - Harfiani, Erna; Suci, Riri Nurul; Arsianti, Ade; Bahtiar, Anton; Basah, Katrin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation in joints. Ageratum conyzoides L. (Babandotan) leaves are proven to be used in inflammation therapy, yet there is a little data regarding the effects of the leaves on RA. The aim of this study is to investigate anti-RA activity of the ethanolic extract of A. conyzoides L. leaves (EEAL) harvested from Bogor, Indonesia, in rats. Methods: The phytochemical screening analysis and thin-layer chromatography were performed to analyze the constituents of the EEAL. This study used white male Sprague Dawley rats which were divided into 6 groups; normal control and negative control groups, both given 0.5% carboxymethyl cellulose; the positive control group, given methotrexate suspension (0.05 mg/200 g bw.); the dose variation extract is 40 mg, 80 mg, and 160 mg/200 g body weight. All the groups were induced with 0.1 ml Complete Freund's adjuvant on day 1, except normal control group. Some parameters will be measured, such as paw edema, levels of leukocyte and lymphocyte, concentrations of tumor necrosis factor-Î± (TNF-Î±), and the number of osteoclasts per mm2. Results: For 21 days the rats have given treated the EEAL in three doses, was showed the decreasing volume of paw edema, levels of blood leukocytes and lymphocytes, concentrations of TNF-Î± and the number of osteoclasts, compared to the rat model of RA. Conclusion: This study showed that the leaves of A. conyzoides L. harvested from Bogor, Indonesia, have activity as anti-RA in a rat model, in which flavonoid plays a role in inhibition of chronic inflammatory processes. Keywords: Ageratum conyzoides L. leaves, Anti-rheumatoid arthritis, Complete Freund's adjuvant, Flavonoids.